An Update and Report Failure of Surgical Syndactyly Repair in Harlequin Ichthyosis. Issue 10 (17th October 2022) - Kahan, Elias H.; Temple, Brian; Carr, Logan; Zellner, Elizabeth
Abstract : Summary: Harlequin ichthyosis (HI) is a rare congenital skin disorder caused by irregular epidermal differentiation. Syndactyly in HI is associated with thick hyperkeratotic skin flexion and angulation deformity of the hand and fingers resulting in limited function of the upper extremity. Traditional syndactyly release is limited as full-thickness skin grafts typically used in reconstruction are composed of diseased skin and require donor sites in a patient predisposed for adverse wound healing. This case report is a follow-up to a previous viewpoint written about digital escharotomies in a newborn with HI and outlines a second and fourth webspace syndactyly release with a dermal substitute. Despite early evidence of adequate release and improved hand function, recurrence of syndactyly was observed within 4 months of surgical release. Our experience described within this case report may suggest the limitations and possible alternatives of surgical release of syndactyly in the HI population.